2008
DOI: 10.3998/ark.5550190.0009.228
|View full text |Cite
|
Sign up to set email alerts
|

Studies of para-quinomethane formation during the tyrosinase-catalyzed oxidation of 4-alkylcatechols

Abstract: UV-Vis spectroscopy, hplc-mass spectrometry and deuterium-labeling studies demonstrate that 4-alkyl-ortho-quinones cleanly rearrange to the isomeric 2-hydroxy-para-quinomethanes over a period of 10-20 minutes in aqueous buffer. These ortho-quinones are much more stable in organic solvents (CD 3 OH, CDCl 3 ). Studies of the rate of rearrangement and of the introduction of pre-formed para-quinomethane to enzyme solution demonstrate that the quinomethanes, formed as secondary products, do not contribute to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…6 We have described other examples of 4-alkylortho-quinones that readily rearrange in aqueous buffer but are relatively stable in organic solvents, with slow formation of complex mixtures. 7 Clearly, the aqueous environment favours proton transfer and para-quinomethane formation. These results for ortho-quinones 9 (Y = Me, NH 2 ) therefore show a consistent pattern of behaviour for derivatives in which the catechol side chain is neither sufficiently nucleophilic to cyclise onto the ortho-quinone ring (Scheme 1) nor sufficiently basic to catalyse rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…6 We have described other examples of 4-alkylortho-quinones that readily rearrange in aqueous buffer but are relatively stable in organic solvents, with slow formation of complex mixtures. 7 Clearly, the aqueous environment favours proton transfer and para-quinomethane formation. These results for ortho-quinones 9 (Y = Me, NH 2 ) therefore show a consistent pattern of behaviour for derivatives in which the catechol side chain is neither sufficiently nucleophilic to cyclise onto the ortho-quinone ring (Scheme 1) nor sufficiently basic to catalyse rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, related to the suicide inhibition of tyrosinase by catechols, we demonstrated the clean rearrangement of 4- n -alkyl- ortho -quinones 2 to para -quinomethanes 3 over a period of 10−20 min in aqueous buffer . Fresh tyrosinase rapidly oxidizes 4- n -alkylcatechols 1 to the corresponding ortho -quinones 2 (Scheme ).…”
Section: Introductionmentioning
confidence: 87%
“…We have had a long-standing interest in the toxicity of ortho-quinones generated by tyrosinase [E.C.1.14. 18.1] activity, in particular because of the possibility of utilizing the action of quinones in selective toxicity to pigment cells in targeted chemotherapy for disseminated malignant melanoma. It was shown that the major cytotoxic product of the noncyclizing tyrosinase substrate 4-hydroxyanisole is the corresponding ortho-quinone, 2,3 and the use of melanogenesis as a targeting strategy in melanoma was proposed.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation